Gold-catalyzed glycosidations: unusual cleavage of the interglycosidic bond while studying the armed/disarmed effect of propargyl glycosides - Kayastha, Abhijeet K.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Armed/disarmed effect of propargyl glycosides in the presence of AuBr(3) is studied. Observed that oxophilic AuBr(3) cleaves interglycosidic bond of an armed disaccharide resulting in the formation of a disaccharide and a 1,6-anhydro sugar. Trisaccharides were obtained after fine tuning the reactivity of the glycosyl donor with different protecting groups. (C) 2010 Elsevier Ltd. All rights reserved.